Scale‐dependent effects of solar radiation patterns on the snow‐dominated hydrologic response. Issue 10 (29th May 2015) - Comola, F.; Schaefli, B.; Ronco, P. Da; Botter, G.; Bavay, M.; Rinaldo, A.; Lehning, M.
Abstract Solar radiation is a dominant driver of snowmelt dynamics and streamflow generation in alpine catchments. A better understanding of how solar radiation patterns affect the hydrologic response is needed to assess when calibrated temperature‐index models are likely to be spatially transferable for ecohydrological applications. We induce different solar radiation patterns in a Swiss Alpine catchment through virtual rotations of the digital elevation model. Streamflow simulations are performed at different spatial scales through a spatially explicit hydrological model coupled to a physically based snow model. Results highlight that the effects of solar radiation patterns on the hydrologic response are scale dependent, i.e., significant at small scales with predominant aspects and weak at larger scales where aspects become uncorrelated and orientation differences average out. Such scale dependence proves relevant for the spatial transferability of a temperature‐index model, whose calibrated degree‐day factors are stable to different solar radiation patterns for catchment sizes larger than the aspect correlation scale.